Role of the global account manager : a boundary role theory perspective - Holt, Sue (Cranfield University, 2003)
As the business environment takes on a global perspective for many business-to- business organisations, so the area of Global Account Management (GAM) has become an increasingly important issue for both researchers and practitioners. This study is focused on providing an in-depth understanding of the characteristics of the roles of global account managers in managing relationships with global customers. This aspect of global account management has received little attention in the literature with little empirical research in the area. From the extant literature on global account management, global account manager roles and relationships in business-to-business markets, a conceptual framework of the global account manager role was constructed. This was supported by role theory, boundary role theory, and theory on the buyer-seller interface. The research was conducted within the realism philosophical paradigm, using a qualitative case study approach with four co-operative case organisations. The research design was also grounded in boundary role theory, with data being collected from the global account managers, their managers, customers and their internal team members in order to provide a rich picture of the role. Semi-structured interviews were used to collect the data and the interviews were analysed against the conceptual framework using a qualitative data analysis package, QSR NVivo. Within-case analyses were carried out followed by a cross-case analysis. This resulted in the presentation of a set of validated role constructs, and a theoretical model of the global account manager role. As well as the main findings from the empirical study, the research also produced some additional findings. The research makes a contribution to theory in two main areas: firstly to our theoretical understanding of global account management roles; and secondly, in extending and supporting existing theory on account management. Given the nature of the research topic, there were also implications for practitioners. Finally the limitations of the research and opportunities for further work were explored.